Analisis Hasil Produksi Perikanan Budidaya Air Tawar di Kebumen Menggunakan Metode Clustering K-means - ikhsanuddin, rohmatulloh muhamad (Institut Teknologi Adhi Tama Surabaya, 2025)
Kebumen, as one of the districts in the south of Central Java Province with an area coverage of 26 sub-districts, has the potential for freshwater aquaculture production to reach 3,316,378 kg in 2022. This production can be optimized by creating clusters in sub-districts in Kebumen to utilize this area. Data mining using the k-means clustering method helps to group sub-district areas so that it can assist in decision making. Tests in data mining using Davies Bouldin with values k=2 to 10 show that the best value results, namely at value k=3, is 0.487. The K-means method with a value of k=3 produces 3 clusters with the result that cluster 1 consists of 19 sub-districts, namely the areas of Petanahan, Bulus Pesantren, Ambal, Mirit, Bonorowo, Prembun, Padureso, Alian, Poncowarno, Kebumen, Pejagoan, Sruweng, Rowokele, Sempor , Gombong, Karanganyar, Karanggayam, Sadang and Karangsambung. Cluster 2 consists of 1 sub-district, namely the Kuwarasan area, while cluster 3 consists of 6 sub-districts, namely the Ayah, Buayan, Puring, Klirong, Kutowinangun and Adimulyo areas.